Experimental Assessment of a Modular Multilevel Converter Using Opal-Rt Control and Power Stages for Low-Frequency Ac Transmission Systems - Travieso-Torres, J; Espina-Gonzalez, E; Diaz-Diaz, M; Uriarte-Gonzalez, M; Ibaceta-Valenzuela, E (Institute of Electrical and Electronics Engineers Inc., 2022)
Modular Multilevel Converters have been proposed for high-voltage direct current and Low-Frequency Alternating Current transmission systems according to benefits associated with their topologies, such as scalability, modularity, high voltage and power capacity. In industrial applications, hundreds of power cells have to be connected in a cascade to reach high-power ratios. However, most of the academic prototypes are equipped with a low number of power cells to validate academic research. Moreover, they are limited to conventional frequency operation in AC ports over the range of 50-60Hz. Hence, this paper presents the experimental results of a Modular Multilevel Converter test-bench comprised of sixty power cells and through OPAL-RT cabinets. Partial results validate a power flow regulation with power factor correction for low-frequency operation at 10-20 HZ. © 2022 IEEE.